Humanistic burden and medical care patterns of real-world patients with myasthenia gravis in Japan - Kasahara-Kiritani, Mami; Saga, Yosuke; Watanabe, Sayuri; Webb, Thomas; Herr, Keira; Yu, DaeYoung; Ringland, Ciara; Birija, Shiva Lauretta; Conyers, Joe; Gibson, Gregor; Hatchell, Niall; Li, Nan (Frontiers in Neurology, 2025)
IntroductionMyasthenia gravis (MG) is a rare autoimmune disease characterized by skeletal muscle weakness. As limited real-world data are available in Japan, we aimed to describe the humanistic burden of disease (primary aim), mainly with regards to health-related quality of life (HRQoL), and treatment patterns (secondary aim) in patients with generalized MG (gMG).MethodsData were drawn from the Adelphi Real World MG Disease Specific Programme™, a cross-sectional survey of neurologists and their patients in Japan from August 2023 and January 2024. Analyses were descriptive.ResultsOverall, 40 neurologists reported data for 128 patients, where 29 patients had self-reported data. Mean (standard deviation) patient age was 57.9 (16.0) years and 53.9% were female. At data collection, 98.4% of patients were receiving maintenance therapy (including novel treatments). Nonsteroidal immunosuppressant therapies were used at first-line of therapy in 54.5% of cases (n = 67/123). Oral systemic steroids were most used [78.0% of patients at first-line (n = 96/123), 77.9% at second-line (n = 53/68), and 75.0% at third-line (n = 15/20)]. The median (IQR) duration from symptom onset to diagnosis was 2.0 (0.9–4.3) months. Of 28 patients with EQ-5D-5L data, 46.4% reported difficulties with usual activities, 42.9% with mobility, 21.4% with self-care, 53.6% with pain/discomfort, and 39.3% with anxiety/depression.ConclusionMost patients in this Japanese cohort with gMG received maintenance therapy and the time from symptom onset to diagnosis was relatively short. However, impaired HRQoL remained.